2017
DOI: 10.1093/hmg/ddw417
|View full text |Cite
|
Sign up to set email alerts
|

Mapping eQTLs with RNA-seq reveals novel susceptibility genes, non-coding RNAs and alternative-splicing events in systemic lupus erythematosus

Abstract: Studies attempting to functionally interpret complex-disease susceptibility loci by GWAS and eQTL integration have predominantly employed microarrays to quantify gene-expression. RNA-Seq has the potential to discover a more comprehensive set of eQTLs and illuminate the underlying molecular consequence. We examine the functional outcome of 39 variants associated with Systemic Lupus Erythematosus (SLE) through the integration of GWAS and eQTL data from the TwinsUK microarray and RNA-Seq cohort in lymphoblastoid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 85 publications
3
38
1
1
Order By: Relevance
“…A recent study reported that the SLE risk variant (rs2663052) also had a splicing QTL effect on WDFY4. 44 However, rs2663052 is not in tight LD with the CADM risk variant (rs7919656, r 2 =0.46 in the Asian samples), and rs2663052 displayed a weaker association signal in CADM in the present study (P=0.0012). A missense variant (rs7097397), which is in moderate LD with rs7919656 (r 2 =0.58 in the Asian samples), may be another candidate causal variant in SLE,42 but the association in CADM was moderate (P=0.0022).…”
Section: Discussioncontrasting
confidence: 72%
“…A recent study reported that the SLE risk variant (rs2663052) also had a splicing QTL effect on WDFY4. 44 However, rs2663052 is not in tight LD with the CADM risk variant (rs7919656, r 2 =0.46 in the Asian samples), and rs2663052 displayed a weaker association signal in CADM in the present study (P=0.0012). A missense variant (rs7097397), which is in moderate LD with rs7919656 (r 2 =0.58 in the Asian samples), may be another candidate causal variant in SLE,42 but the association in CADM was moderate (P=0.0022).…”
Section: Discussioncontrasting
confidence: 72%
“…DNA demethylation has been found in SLE CD4 þ T cells, but not in either CD8þT cells or other mononuclear white blood cells [71,72]. Moreover, an impaired DNA methylation of the inactive X-chromosome was suggested to explain, at least in part, the female prevalence of the disease micro-and long non-coding RNA expression are though to contribute to the pathogenesis of SLE [73]. Since SLE, as most autoimmune diseases, is characterized by a female predominance, the X chromosome was hypothesized to be involved in the disease pathogenesis, as in other autoimmune diseases [74,75].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Although the number of patients in both studies was not large, an analysis of these groups over time might enable the development of personalized therapies for SLE patients [22]. Furthermore, the emergence of next-generation sequencing technologies such as RNA sequencing has provided higher resolution in gene expression measurements together with identification of alternative splicing events, noncoding RNAs, and novel loci in SLE [23]. Technological advances including deep sequencing have offered novel high-throughput platforms that will help to decipher the molecular pathways contributing to SLE pathogenesis.…”
Section: Genetics and Slementioning
confidence: 99%